Learning Systems Biology: Conceptual Considerations toward a Web-Based Learning Platform - Matthias Dehmer; Fernando Lyardet; Frank Emmert-Streib (MDPI AG, 2013)
Within recent years, there is an increasing need to train students, from biology and beyond, in quantitative methods that are relevant to cope with data-driven biology. Systems Biology is such a field that places a particular focus on the functional aspect of biology and molecular interacting processes. This paper deals with the conceptual design of a web-based course and its content for educating students in systems biology. We discuss several learning strategies and problems when dealing with structural hypertext patterns that might occur in the context of web-based learning platforms. Finally, we explain the content of the course modules and its features such as its usability and the impact on the learner.